2007
DOI: 10.1007/s00125-007-0737-6
|View full text |Cite
|
Sign up to set email alerts
|

Continuous stimulation of human glucagon-like peptide-1 (7–36) amide in a mouse model (NOD) delays onset of autoimmune type 1 diabetes

Abstract: Aims/hypothesis We examined the effect of glucagon-like peptide-1 (GLP-1) on the development of diabetes and islet morphology in NOD mice by administering GLP-1 to prediabetic mice. Methods Eight-week-old female NOD mice were infused subcutaneously with human GLP-1 via a mini-osmotic pump for 4 or 8 weeks. In mice treated with GLP-1 for 4 weeks, blood glucose levels and body weight were measured. An intraperitoneal glucose tolerance test (IPGTT) and evaluation of insulitis score were also performed. Beta cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 44 publications
2
42
0
1
Order By: Relevance
“…Consistent with the results reported by Hogan et al, GLP-1R agonists have previously been shown to increase cAMP formation in multiple lymphocyte populations in a GLP-1R-and exendin (9-39)-dependent manner [5]. Furthermore, several reports have described disease remission and enhanced numbers of regulatory T cells in experimental murine models of autoimmune type 1 diabetes treated with GLP-1R agonists in the absence of concomitant therapy with immunomodulatory agents [6,7]. GLP-1R activation also modestly reduced stromal cell-derived factor-1-enhanced lymphocyte migration in human CD4 + lymphocytes [8], whereas genetic disruption of Glp1r produced detectable defects in thymocyte and lymphocyte proliferation following stimulation ex vivo [5].…”
supporting
confidence: 75%
“…Consistent with the results reported by Hogan et al, GLP-1R agonists have previously been shown to increase cAMP formation in multiple lymphocyte populations in a GLP-1R-and exendin (9-39)-dependent manner [5]. Furthermore, several reports have described disease remission and enhanced numbers of regulatory T cells in experimental murine models of autoimmune type 1 diabetes treated with GLP-1R agonists in the absence of concomitant therapy with immunomodulatory agents [6,7]. GLP-1R activation also modestly reduced stromal cell-derived factor-1-enhanced lymphocyte migration in human CD4 + lymphocytes [8], whereas genetic disruption of Glp1r produced detectable defects in thymocyte and lymphocyte proliferation following stimulation ex vivo [5].…”
supporting
confidence: 75%
“…For example, chronic administration of exendin-4 to NOD mice leads to modest and significant decrease in insulitis [29]. Continuous infusion of GLP-1 also delayed the onset of diabetes in NOD mice [30]. Other studies have used exendin-4 in combination with anti-inflammatory agents to demonstrate a more significant blocking of insulitis and diabetes onset in NOD mice [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…47 GLP-1 has also been recently investigated for its potential benefit in the treatment of type-1 diabetes. Zhang et al 5 have demonstrated that continuous infusion of GLP-1 in pre-diabetic NOD mice results in significant delay in the onset of diabetes as a result of increased beta-cell proliferation coupled with decrease in beta-cell apoptosis. Furthermore, combination therapies using GLP-1 or exendin-4 with gastrin, 48 anti-lymphocyte serum 49 or anti-CD3 immunotherapy 50 have been shown to restore normoglycemia in acutely diabetic NOD mice by increasing insulin stores and reducing beta-cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…1 GLP-1 promotes the maintenance of beta-cell mass through stimulation of cell proliferation and neogenesis while inhibiting apoptosis, [2][3][4] and has been shown to be effective in reducing diabetes incidence in models of type-1 diabetes. 5 In addition to its effects on beta-cell survival and growth, GLP-1 acutely stimulates glucose-dependent insulin secretion and can increase insulin gene expression through several mechanisms including upregulation of the transcription factor pancreatic duodenal homeobox-1 (Pdx-1). [6][7][8] GLP-1 also reduces blood glucose levels by inhibiting glucagon secretion from alpha-cells, an effect likely mediated through increased somatostatin release from delta-cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation